Functional state of cardiovascular system in highly-skilled swimmers at latitudinal displacement - Apokin, V. V.; Pavlovskaya, V. S.; Povzun, V. D. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to assess changes in the adaptive and functional capabilities of highly-skilled athletes at latitudinal displacement. Methods and structure of the study. We evaluated the functional state of the cardiovascular system in the male swimmers of the same age group qualified not lower than Masters of Sport right after the flight through several time zones and three weeks after their stay outside their habitual time zone. Their response to the exercise experienced was evaluated based on the selected indicators and indices that reflect the state of both adaptive capabilities and functional capacity of the cardiovascular system. Results and conclusions. The analysis of the dynamics of changes in the hemodynamic indices revealed that, on the one hand, the displacement of the central regulatory mechanisms in the examined group was adequate enough to optimize the functional reserves, while the current vegetative status contributed to the economization of energy resource, thus shifting the hemodynamic load towards the vascular bed. This means that the regulatory adjustments in this group were optimal.